Internet Content-based Activities for Empowering Listening Comprehension to the First Semester Students of English Department State Polytechnic of Sriwijaya Palembang - Yusri Yusri (ELTE Journal (English Languange Teaching and Education), 2015)
AbstractThis study was conducted to find out (1) whether or not it is effective empowering students’ listening comprehension through Internet Content-Based Activities. The samples of this study were the first  semester students of English Department State Polytehcnic of Sriwijaya Palembang in the academic year of 2013-3014. The primary data were collected by means of test. The results show that  there was a statistically significant difference in listening comprehension achievement of the students pretest-posttest after being taught through Internet Content-Based Activities. It was found out that the average score of the students’ pre- test was 65.33 while in the post test was 74.19. the result of t-test calculation shows  that the value of t was 6.472. Where the value of the t-table 2.086  at the significance level of 0,05% with df 20. Thus, t-obtained was higher than t-table. It can be concluded that Internet Content-Based Activities was effective empowering the first semester, English department  students’ listening comprehension at State Polytechnic of Sriwijaya Palembang. Key Words : Internet Content-Based Activities, Listening Comprehension